A review of subtidal kelp forests in Ireland: From first descriptions to new habitat monitoring techniques. Issue 13 (16th June 2020) - Schoenrock, Kathryn M.; Chan, Kenan M.; O'Callaghan, Tony; O'Callaghan, Rory; Golden, Aaron; Krueger‐Hadfield, Stacy A.; Power, Anne Marie
Abstract: Aim: Kelp forests worldwide are important marine ecosystems that foster high primary to secondary productivity and multiple ecosystem services. These ecosystems are increasingly under threat from extreme storms, changing ocean temperatures, harvesting, and greater herbivore pressure at regional and global scales, necessitating urgent documentation of their historical to present‐day distributions. Species range shifts to higher latitudes have already been documented in some species that dominate subtidal habitats within Europe. Very little is known about kelp forest ecosystems in Ireland, where rocky coastlines are dominated by Laminaria hyperborea . In order to rectify this substantial knowledge gap, we compiled historical records from an array of sources to present historical distribution, kelp and kelp forest recording effort over time, and present rational for the monitoring of kelp habitats to better understand ecosystem resilience. Location: Ireland (Northern Ireland and Éire). Methods: Herbaria, literature from the Linnaean society dating back to late 1700s, journal articles, government reports, and online databases were scoured for information on L. hyperborea . Information about kelp ecosystems was solicited from dive clubs and citizen science groups that are active along Ireland's coastlines. Results: Data were used to create distribution maps and analyze methodology and technology used to record L. hyperborea presence and kelp ecosystems within Ireland. We discuss the recent surge in studies on Irish kelp ecosystems, fauna associated with kelp ecosystems that may be used as indicators of ecosystem health and suggest methodologies for continued monitoring. Main Conclusions: While there has been a steady increase in recording effort of the dominant subtidal kelp forest species, L. hyperborea, only recently have studies begun to address other important eco‐evolutionary processes at work in kelp forests including connectivity among kelp populations in Ireland. Further monitoring, using suggested methodologies, is required to better understand the resilience of kelp ecosystems in Ireland. Abstract : Laminaria hyperborea is a marine ecosystem engineer that structures sub‐tidal kelp forests in Europe. In Ireland this species has been recorded since 1913, but kelp ecosystem function and resilience is not well understood. This review provides analysis of kelp records and the few ecosystem studies that exist to suggest future areas of research to better understand and protect these natural resources.